2019
DOI: 10.3390/rs11202429
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Pattern of Soil Erosion Drivers and the Contribution Rate of Human Activities on the Loess Plateau from 2000 to 2015: A Boundary Line from Northeast to Southwest

Abstract: The Loess Plateau is one of the most fragile areas in the world, where the problem of soil erosion is particularly prominent. The spatial and temporal variation characteristics and mechanisms of soil erosion in this region have always been hot topics for researchers. In this study, Revised Universal Soil Loss Equation (RUSLE) is used to estimate the soil erosion modulus of the Loess Plateau from 2000 to 2015, the dynamic characteristics of its temporal and spatial variations and driving mechanisms are determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…It should be noted that the 400 mm isohyet is of great significance to the physical geography and socio-economic regionalization in China, and it coincides with the Huhuanyong Line. In addition to dividing the climatic zones, this line divides the forest vegetation from the grassland vegetation and the densely populated area from the sparsely populated area [31,32].…”
Section: Study Areamentioning
confidence: 99%
“…It should be noted that the 400 mm isohyet is of great significance to the physical geography and socio-economic regionalization in China, and it coincides with the Huhuanyong Line. In addition to dividing the climatic zones, this line divides the forest vegetation from the grassland vegetation and the densely populated area from the sparsely populated area [31,32].…”
Section: Study Areamentioning
confidence: 99%
“…From the spatial regression model, we found that the value of ecosystem services is affected by its grid cell elements but also by neighboring grid cells or more distant grid cell elements. This means that the concentration of population and economy does not automatically lead to the degradation of ecological services [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abundant studies have been conducted on human-induced erosion, and most of the research has been concentrated on areas in the Loess Plateau (X. J. Guo & Shao, 2019;H. C. Li, Guan, et al, 2022;Zare et al, 2017) and the southern region (N. Li, Zhang, et al, 2022;L.…”
Section: Introductionmentioning
confidence: 99%